2021
DOI: 10.1002/anie.202111239
|View full text |Cite
|
Sign up to set email alerts
|

A Solvent‐Polarity‐Induced Interface Self‐Assembly Strategy towards Mesoporous Triazine‐Based Carbon Materials

Abstract: Triazine-based materials with porous structure have recently received numerous attentions as af ascinating new class because of their superior potential for various applications.H owever,i ti ss till af ormidable challenge to obtain triazine-based materials with precise adjustable meso-scaled pore sizes and controllable pore structures by reported synthesis approaches.H erein, we develop as olvent polarity induced interface self-assembly strategy to construct mesoporous triazine-based carbon materials.I nt his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…performance of porous organic polymers in practical gas adsorptive separation applications. Single-component physisorption isotherms for CO 2 , N 2 and CH 4 were systematically analyzed via volumetric methods at 273.15 K and 298.15 K, and the CO 2 /N 2 and CO 2 /CH 4 gas pairs were comprehensively calculated by employing the initial slope ratios from Henry's law constants of the pure gas adsorption isotherms at the same temperature and low-pressure coverage of less than 0.3 bar, as PVAm/PZEA-Pro/PZEA-Sar (210), 68 MPC-500 (140), 69 PIP-CMC/ TMC (119), 70 and PIM-PI-1 (57.2), 71 the CO 2 /N 2 value of polymer 1 is comparable or exceeds those of CTFs (14.2-20.3), 72 PPFs (14.5-15.4), 73 MF-168-600 ( 16), 74 and PIM-1 S A /S B (12.7) 75 at 273.15 K and HC PPO-Br (20), 76 CCP-6 ( 17), 77 UiO-66 (16.7), 78 Sg (9.9), 79 and SBL-MIP-C-800 (9.5) 29), 87 PIM-Cardo-TOT (25.5), 88 Cu-1 (9), 89 and Ni-MOF (2.9) 90 at 298.15 K. In addition, it should be particularly pointed out that the selective uptake of CO 2 over N 2 and CH 4 is mainly induced by the strong dipole-quadrupole interaction between the structurally accessible polar functional groups, heteroatoms and CO 2 molecules as well as the quadrupole-quadrupole interactions among the CO 2 molecules. On account of the systematic studies above, it has been demonstrated that the utilized carbonates are a family of lowcost and accessible candidates for preparing novel and highly porous hyper-cross-linked polymers possessing hierarchical architectures, versatile functionalities, enhanced gas uptake capacities and adsorption selectivities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…performance of porous organic polymers in practical gas adsorptive separation applications. Single-component physisorption isotherms for CO 2 , N 2 and CH 4 were systematically analyzed via volumetric methods at 273.15 K and 298.15 K, and the CO 2 /N 2 and CO 2 /CH 4 gas pairs were comprehensively calculated by employing the initial slope ratios from Henry's law constants of the pure gas adsorption isotherms at the same temperature and low-pressure coverage of less than 0.3 bar, as PVAm/PZEA-Pro/PZEA-Sar (210), 68 MPC-500 (140), 69 PIP-CMC/ TMC (119), 70 and PIM-PI-1 (57.2), 71 the CO 2 /N 2 value of polymer 1 is comparable or exceeds those of CTFs (14.2-20.3), 72 PPFs (14.5-15.4), 73 MF-168-600 ( 16), 74 and PIM-1 S A /S B (12.7) 75 at 273.15 K and HC PPO-Br (20), 76 CCP-6 ( 17), 77 UiO-66 (16.7), 78 Sg (9.9), 79 and SBL-MIP-C-800 (9.5) 29), 87 PIM-Cardo-TOT (25.5), 88 Cu-1 (9), 89 and Ni-MOF (2.9) 90 at 298.15 K. In addition, it should be particularly pointed out that the selective uptake of CO 2 over N 2 and CH 4 is mainly induced by the strong dipole-quadrupole interaction between the structurally accessible polar functional groups, heteroatoms and CO 2 molecules as well as the quadrupole-quadrupole interactions among the CO 2 molecules. On account of the systematic studies above, it has been demonstrated that the utilized carbonates are a family of lowcost and accessible candidates for preparing novel and highly porous hyper-cross-linked polymers possessing hierarchical architectures, versatile functionalities, enhanced gas uptake capacities and adsorption selectivities.…”
Section: Resultsmentioning
confidence: 99%
“…The data summarized in Table 3 show that the CO 2 /N 2 sorption selectivities are about 20.16, 19.84, and 19.02 at 273.15 K, which theoretically drop to 15.71, 18.12, and 18.00 at 298.15 K from polymer 1 to polymer 3 , respectively. Notably, among the polymers, polymer 1 shows the best sorption selectivity of CO 2 over N 2 at 273.15 K. Although this value is much lower than those of PVA/PAA-C 3 H 7 (341), 67 PVAm/PZEA-Pro/PZEA-Sar (210), 68 MPC-500 (140), 69 PIP-CMC/TMC (119), 70 and PIM-PI-1 (57.2), 71 the CO 2 /N 2 value of polymer 1 is comparable or exceeds those of CTFs (14.2–20.3), 72 PPFs (14.5–15.4), 73 MF-168-600 (16), 74 and PIM-1 S A / S B (12.7) 75 at 273.15 K and HC PPO-Br (20), 76 CCP-6 (17), 77 UiO-66 (16.7), 78 Sg (9.9), 79 and SBL-MIP-C-800 (9.5) 80 at 298.15 K. Likewise, the data collected in Table 3 show that the CO 2 /CH 4 sorption selectivities are theoretically predicted to be about 41.84, 40.22, and 35.08 at 273.15 K and 35.98, 36.14, and 33.64 at 298.15 K for polymer 1 to polymer 3 , respectively. Notably, polymer 1 among these polymers exhibits the highest gas adsorption selectivity of CO 2 over CH 4 at 273.15 K, which is superior to those of Tg-AzoCOF (37), 81 NGA (21.4), 82 MOPI-6-0.5 (18), 83 BOP-1 (5.48), 84 and NPC-1 (3.8) 85 at 273.15 K, and S-D-1.6 (34), 86 CuDTTA (29), 87 PIM-Cardo-TOT (25.5), 88 Cu-1 (9), 89 and Ni-MOF (2.9) 90 at 298.15 K. In addition, it should be particularly pointed out that the selective uptake of CO 2 over N 2 and CH 4 is mainly induced by the strong dipole–quadrupole interaction between the structurally accessible polar functional groups, heteroatoms and CO 2 molecules as well as the quadrupole–quadrupole interactions among the CO 2 molecules.…”
Section: Resultsmentioning
confidence: 99%
“…and photocatalysis), combing with renewable energy, which is potentially featured with energy-saving and zero-emission characteristics, has attracted increasing attention recently. [8][9][10][11][12] Especially, the electrocatalytic nitrogen reduction reaction (eNRR) involves a simple process to directly reduce nitrogen (N 2 ) molecules and yield ammonia in an aqueous solution and under ambient conditions, which is exceptionally energyefficient, eco-friendly, and sustainable. [13] Similar to the H-B process, eNRR inherits the high kinetic barrier for nitrogen activation.…”
Section: Introductionmentioning
confidence: 99%
“…[30,33] On the other hand, surfactants tend to assemble into ordered shaped micelles, which can be further arranged into larger assemblies in solution under appropriate condition. [10,34,35] Such special assembly property makes it an ideal template for the crystallization and growth of noble metals. [17] Open mesopores will form after the removal of surfactants, which endow materials with considerable properties, benefiting from the high surface area and the 3D accessibility for molecules, extensively facilitating mass and electron transfer process.…”
Section: Introductionmentioning
confidence: 99%